Pertimbangan Hakim Pengadilan Agama Tentang Perceraian dengan Alasan Pisah Rumah Singkat (Studi Putusan Nomor 375 Pdt.G/2024/PA.Plk) - Tambun, Putri Cicilia; Wardhani, Novea Elysa; Noor, Syamhudian (UIR Press, 2025)
The inequality of divorce procedures in KHI and Law No. 1 of 1974 prompted the issuance of SEMA No. 3 of 2023 as a refinement of the formulation of SEMA No. 1 of 2022. This SEMA provides strict guidelines on the minimum separation requirement of six months to grant a divorce, except for the element of domestic violence. Using a qualitative approach with normative legal interpretation, this research examines the legal construction and legal considerations of judges in resolving divorce cases. First, SEMA Number 3 Year 2023 has proven to be an effective tool in realising a legal system that is reliable, fair, and able to provide substantive legal protection to litigants in religious courts. Second, although SEMA No. 3 of 2023 regulates a minimum separation of six months, judges can still grant divorce in cases with a shorter separation time if there is evidence of verbal domestic violence.